Mucosal Lichen Planus: A Clinical Study of 145 Patients - Aşkın, Özge; Özkoca, Defne; Üstünbaş Uzunçakmak, Tuğba Kevser; Kutlu, Özce; Engin, Burhan; Kutlubay, Zekayi (Cerrahpaşa Medical Journal, 2021)
Objective: Lichen planus is a disease of unknown origin that affects the skin and the mucous membranes; the oral mucosa is affected in particular. In this study, we aim to demonstrate the demographic characteristics, preferred localizations, and subtypes of mucosal lichen planus lesions and to examine the relationship between these variables. Methods: Patients with a definitive histopathological diagnosis of oral or genital lichen planus were included in this retrospective study. Age, gender, localization, clinical subtype (erosive/keratotic), differential diagnosis, cutaneous involvement status, and hepatitis C virus (HCV) infection status of each patient were noted, and the statistical analysis was performed with SPSS version 21. Results: A total of 145 patients were included in this study; 70 (48.3%) were female and 75 (51.7%) were male; 133 (91.7%) were located in the oral mucosa and 12 (8.3%) were located in the genital mucosa; 98 (67.6%) were erosive and 47 (32.4%) were keratotic. Cutaneous involvement was present in 15 (10.3%) of the patients and 130 (89.7%) did not have cutaneous involvement. Conclusion: Our oral lichen planus patient series was similar to the previous literature in terms of age and localization; however, we observed a male predominance, unlike the previous articles. HCV positivity was not observed in any of our patients. Cite this article as: Aşkın Ö, Özkoca D, Uzunçakmak TKU, Kutlu Ö, Engin B, Kutlubay Z. Mucosal lichen planus: A clinical study of 145 patients. Cerrahpaşa Med J. 2021;45(2):124-128.